THE EXISTENCE OF GO-LAB AS A LEARNING PLATFORM BASED INQUIRY LEARNING SPACES IN ENHANCING SCIENCE LITERACY OF STUDENTS - Rangga Alif Faresta; M. Zainal Abidin (FKIP Universitas Samawa, 2023)
Based on the PISA data in 2018, shows that the science literacy of students in Indonesia is still considered low. One of the causes is the choice of teaching materials that are not contextual and do not facilitate students in developing their literacy skills. Go-labs is a media learning platform based on Inquiry (Inquiry Learning Space), where its use can help students improve their science literacy skills. The purpose of this research is to find out more about the effect of inquiry-based learning models and the use of learning media on improving science literacy in students. The method used is a literature study in the form of scholarly articles indexed on Google Scholar. The results of the literature study show that the use of inquiry-based learning models has been scientifically proven to improve science literacy skills in students. The same goes for the use of Go-Labs as a learning media with Inquiry Learning Space features. Therefore, the use of Go-Labs can be used as one of the learning media options to improve science literacy in students.